Perancangan Buku Panduan Permainan Bola Basket 2017 Berbasis Fotografi - rofi'i rofi'i; Pujiyanto Pujiyanto; Ahmad Zakiy Ramadhan (LPPM STIKI Malang, 2019)
FIBA Rules book on 2017 which is a handbook basketball rules. The book explains all the rules in detail starting from basic rules until the rules are common. This book should be used as a tool for the players to know the rules of play in the game of basketball, but in fact this book is only used by the referee as a tool to run a game. This is causing a lot of players when the program will often perform a fundamental error. The fundamental error committed players make a match less healthy due to too many abuses. Photography books made to describe a State of basketball rules published in the book the FIBA Rules 2017. In this final task process designer that needs to be done is to identify data from primary data source and secondary data sources the next step draw a conclusion from the data already obtained. After the conclusion of the finished drawn an answer for a foothold. After the process is done footing the concept design and process design, and then done the digitization phase to the final design.The result of this design is the result of a media education basketball rules. With the design of the book Guide basketball games 2017 Based Photography is expected to give an education to the players in order to produce a quality game.